(untitled) (CaJoST, 2023)
The development of biologically inspired silver nanoparticles (AgNPs) has attracted considerable worldwide attention in the field of medical nanotechnology. This is because secondary metabolites possess the unique reducibility required in the green synthesis of nanoparticles. This study for the first time describes the use of an aqueous extract of Lagenaria breviflora leaves (LBaq) in the synthesis of AgNPs. The methanolic extract of Lagenaria breviflora leaves (LBme) was analyzed to determine the presence of some important phytochemicals. AgNPs were prepared at different concentrations, using the green-synthetic method. The synthesized AgNPs were characterized using UV-Visible Spectrophotometer (UV-Vis), Energy Dispersive X-ray Spectrometry (EDS), Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). Qualitative phytochemical analysis of the methanolic extract of Lagenaria breviflora leaves confirmed the presence of flavonoids, terpenoids, saponins, alkaloids and cardiac glycosides. A colour change from light yellow to dark/reddish-brown colouration after 6 hours indicated the formation of AgNPs, which was confirmed by a maximum absorption band observed at almost 450 nm in the UV-Vis spectrum. The crystalline nature of AgNPs was confirmed by the XRD pattern. The SEM results revealed the morphology of the synthesized AgNPs including some oval and nano-sphere-shaped particles. The EDS analysis confirmed the presence of elemental silver in abundance. AgNPs were successfully obtained from the bioreduction of AgNO3 solution using LBaq. The results obtained in this study prove that Lagenaria bleviflora leaves possess the bioreducing ability required to synthesize silver nanoparticles at the nanoscale level.